Canon ImagePROGRAF IPF6100. - Oliveros, Luis Anthony G.
An article featuring Canon ImagePROGRAF IPF6100, an easy-to-use large format printer that gives optimum quality prints.
Keywords: Computer ? peripherals ? printers